Evaluation of Mechanical Characteristics of Tungsten Inert Gas (TIG) Welded Butt Joint of Inconel 600 - Arash Moradi; Fatemeh Marashi Najafi; Yong Chen; Mahmoud Chizari (Journal of Manufacturing and Materials Processing, 2025)
Inconel 600 alloy has gained consideration as a favourable material for heat and power applications, particularly in turbine blades, due to its superior mechanical behaviour encompassing strength, toughness, oxidation resistance, and ductility. Tungsten Inert Gas (TIG) welding is one of the preferred techniques for joining these alloys. Therefore, the investigation of the mechanical behaviour after the welding process is crucial for selecting the appropriate technique for joining Inconel 600 sheets. This research focuses on investigating the microstructure and mechanical behaviour of TIG-welded Inconel 600 through a series of tests, such as tensile, fatigue, creep, and hardness evaluations. In addition, microstructural analysis is combined with these mechanical evaluations to simulate the operating conditions experienced by turbine blades. Key parameters such as yield strength, tensile strength, and elongation have been evaluated through these analyses. The Ramberg–Osgood relationship has been investigated using the engineering and true stress–strain curves obtained from the welded specimens. The results of the fatigue test illustrate the relationship between strain amplitude and the number of cycles to failure for single and double-edge notched specimens. The test was performed at two different loads including 400 MPa and 250 MPa at a constant temperature of 650 °C, and the corresponding strain-time curves were recorded. The results showed rapid creep failure at 650 °C, suggesting that TIG welding may need to be optimized for high temperature applications.